Role of uterine artery Doppler indices for predicting intrauterine pathology inconclusive on 2-dimensional transvaginal imaging among infertile women undergoing frozen embryo transfer cycle - Sindhu, Lavi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Objective of current study was to correlate uterine artery Doppler parameters with endometrial findings on hysteroscopy and its importance for the prediction of intrauterine pathology inconclusive on 2-dimensional transvaginal imaging prior to frozen embryo transfer. Methods: This was a retrospective study conducted at Medicover fertility center, New Delhi, India. The study population comprised of women with infertility who have undergone hysteroscopy before frozen embryo transfer. Total 70 patients were recruited based on inclusion/exclusion criteria. Intrauterine pathology found in 57.2% (n= 40) patients and 42.8% (n=30) had normal endometrial cavity on hysteroscopy, they were categorized as group 1 and group 2 respectively based on their findings. Both the groups were compared for pre hysteroscopy uterine artery Doppler parameters, resistivity index and pulsatility index. Further clinical pregnancy rate and miscarriage rate were determined in both groups. Results: Both the groups were comparable for age, body mass index, duration, and type of infertility. Mean RI and PI was significantly higher in group 1 as compared to group 2 (0.90±0.025, 2.89±0.291 vs. 0.76±0.043, 1.82±0.27; p value <0.001). The best cut-off value of uterine artery RI was ≥0.87 with sensitivity of 90% (95% CI=0.7634-0.9721), specificity of 100% (95% CI=0.8843-1.0000) and PI was 2.46 with sensitivity of 100% (95% CI=0.9119-1.0000), specificity of 96.7% (95% CI=0.8278-0.9992). Conclusions: Uterine artery Doppler is a non-invasive, cost- effective useful add-on tool for routine endometrial evaluation and can be a good predictor for screening intrauterine pathology and valuable in decision making for pre-IVF hysteroscopy.